2011
DOI: 10.1016/j.ejso.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy to direct treatment in gastric cancer. A systematic review of the literature

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. analyses showed that the combination of dye and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Such sentinel node-based surgery (sentinel node navigation surgery) could be helpful in detecting possible LNM that requires radical surgery as well as obviating the need for radical surgery in those with a negligible risk of LNM. The sensitivity of sentinel lymph node biopsy and the incidence of skip metastasis have been reported to be anywhere between 45·5 and 100 per cent, and 0 and 11·8 per cent respectively 23 . The problems of false-negative and skip metastasis should be addressed to ensure that a combination of limited lymph node dissection and endoscopic surgery can be applied appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Such sentinel node-based surgery (sentinel node navigation surgery) could be helpful in detecting possible LNM that requires radical surgery as well as obviating the need for radical surgery in those with a negligible risk of LNM. The sensitivity of sentinel lymph node biopsy and the incidence of skip metastasis have been reported to be anywhere between 45·5 and 100 per cent, and 0 and 11·8 per cent respectively 23 . The problems of false-negative and skip metastasis should be addressed to ensure that a combination of limited lymph node dissection and endoscopic surgery can be applied appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Early gastric cancer, defined as a malignant gastric lesion limited to the submucosal layer, has been traditionally treated by radical gastrectomy in association with lymph node dissection; however, the low rates of positive lymph nodes in association with the increased risk of perioperative complications enabled the surgeons to look for a less invasive method in order to treat early gastric cancer patients 15,16 . For example, it is estimated that up to 97% of cases diagnosed with early gastric cancer will not benefit from extended lymph node dissection, while the perioperative complication rates remain high 17 . In consequence, the concept of sentinel lymph node biopsy was proposed.…”
Section: Lymphatic Spread In Gastric Cancermentioning
confidence: 99%
“…Therefore, some different therapeutic strategies and opinions have been developed. For example, while in Netherlands the first line therapeutic option is represented by radical gastrectomy with extended lymph node dissection, in the Eastern countries this protocol is rarely encountered 17,21 . In consequence, the Eastern scientists have widely investigated and later on introduced in the standard therapeutic protocol the sentinel lymph node biopsy protocol 22,23 .…”
Section: East Versus West Againmentioning
confidence: 99%
“…Subgroup analyses of meta-analyses showed that the combination of dye and radioactive colloid detection substances is better for detection. (8,9) Either way, adequate training is required as is evident. (10-12)…”
Section: Matters Of Debatementioning
confidence: 99%